The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.21273/horttech03483-16
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Mower Saves Energy and Improves Quality of Tall Fescue Lawn

Abstract: Battery-powered autonomous mowers are designed to reduce the need of labor for lawn mowing compared with traditional endothermic engine mowers and at the same time to abate local emissions and noise. The aim of this research was to compare autonomous mower with traditional rotary mower on a tall fescue (Festuca arundinacea) lawn under different nitrogen (N) rates. A two-way factor experimental design with three replications was adopted. In the study, four N rates (0, 50, 100,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 4 publications
(7 reference statements)
2
34
1
Order By: Relevance
“…A small ordinary gasoline engine has an efficiency ranging from 20% to 25%, although it uses primary energy, while the efficiency of the Italian National Electric System is 46%. However, the primary energy consumption measured in this trial differs from that measured by Grossi et al [12], who compared an Automower 330X and a John Deere walk-behind mulching rotary mower. The Automower required 4.80 kWh/week of primary energy to cover 1296 m 2 , while the John Deere required 12.60 kWh/week.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…A small ordinary gasoline engine has an efficiency ranging from 20% to 25%, although it uses primary energy, while the efficiency of the Italian National Electric System is 46%. However, the primary energy consumption measured in this trial differs from that measured by Grossi et al [12], who compared an Automower 330X and a John Deere walk-behind mulching rotary mower. The Automower required 4.80 kWh/week of primary energy to cover 1296 m 2 , while the John Deere required 12.60 kWh/week.…”
Section: Discussioncontrasting
confidence: 62%
“…The height and frequency of mowing were performed in order to respect the "1/3 rule", which means that mowing does not involve more than one third of the total height of the grass, in order to prevent scalping and physiological stress [11]. The most widespread lawnmowers in Italy are electric rotary mowers for small gardens and gasoline-powered rotary mowers for larger gardens [12]. However, autonomous mowers are becoming more common.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors [1] claim that flail mowers cannot equal the mowing quality of reel mowers nor rotary mowers, while Parish and Fry [11] have observed that, if a flail mower is properly sharpened, it may produce the same turf quality and mowing quality of a rotary 2 of 6 mower. In Italy, the maintenance of home lawns is usually carried out with rotary mowers [12]. Rotary mowers can be powered by gasoline engines or by electric engines.…”
Section: Introductionmentioning
confidence: 99%
“…Rotary mowers can be powered by gasoline engines or by electric engines. Electric rotary mowers are usually supplied using an electric cord or a battery [12]. Until a few years ago, the only electric rotary mowers used for private lawns in Italy were supplied with a cord.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile robot solutions are not widely available on the market today. The most popular and most affordable ones are feeding robots in barns (Lely Juno 100), lawn mowers (Husqvarna Automower) (Grossi et al, 2016) and drones for field imaging in precision agriculture. Scientific articles discuss numerous mobile robot designs.…”
Section: Introductionmentioning
confidence: 99%